Functional Status and Instrumental Activities of Daily Living After Transcatheter Aortic Valve Replacement. Issue 2 (April 2021) - Fukui, Shogo; Kawakami, Michiyuki; Hayashida, Kentaro; Ishikawa, Aiko; Mori, Naoki; Oguma, Yuko; Fukuda, Keiichi; Tsuji, Tetsuya
Abstract : The purpose of this study was to investigate changes over time in instrumental activities of daily living (IADL), physical function, physical frailty, cognitive function, and nutritional status after transcatheter aortic valve implantation (TAVI). Fifty consecutive older patients with aortic stenosis as possible candidates for TAVI were prospectively enrolled. Their average age was 84.6 ± 3.1 years, and 39 (78%) were female. The results of the linear mixed-effects model for the isometric knee extension muscular strength showed a significant change. IADL and nutritional status were significantly different preoperatively compared with 6 months postoperatively after transfemoral TAVI.